Modeling the Fonnation of Bainitic Ferrite in Low-carbon Steels (The Minerals, Metals and Materials Society, 2003)
In low carbon TRIP steels, the formation of carbide-free bainitic ferrite is crucial for the stabilization of austenite. Based on experimental investigations modeling the bainite reaction is examined adopting diffusional and displacive mechanisms, as well as the semi-empirical JMAK approach. Transformation tests were carried out to study the isothermal austenite decomposition into bainitic ferrite for a model steel containing 0.6wt%C, 1.5wt%Mm and 1.5wt%Si which replicates the composition of remaining austenite at the start of the bainite reaction in a classical C-Mn-Si TRIP steel. In the diffusional approach, classical nucleation theory is employed and subsequent growth of bainite plates is modeled using the Zener-Hillert theory. In the displacive approach, the autocatalytic nucleation of bairtite plates is assumed to be rate controlling. The predictive capability of all models is evaluated for temperature ranges where different morphologies of bainitic ferrite have been detected, The shortcomings and inherent challenges associated with either of these modeling approaches will be delineated.